Windows Server 2012 security from end to edge and beyond architecting, designing, planning, and deploying Windows Server 2012 security solutions - Shinder, Thomas W. (Elsevier/Syngress, 2013)
Provides practical examples of how to design and deploy a world-class security infrastructure to protect both Windows 8 and non-Microsoft assets on your system. Written by two Microsoft employees who provide an inside look at the security features of Windows 8.